Role of Grain Size and Shape in Superplasticity of Metals - Lu, Zhaoyang; Huang, Xuqiang; Huang, Jingzhe (Frontiers in Materials, 2021)
Superplasticity is characterized by an elongation to failure of >300% and a measured strain rate sensitivity (SRS), close to 0.5. The superplastic flow is controlled by diffusion processes; it requires the testing temperature of 0.5Tm or greater where Tm is the absolute melting temperature of metals. It is well established that a reduction in grain size improves the optimum superplastic response by lowering the deformation temperature and/or raising the strain rate. The low-temperature superplasticity (LTSP) is attractive for commercial superplastic forming, in view of lowering energy requirement, increasing life for conventional or cheaper forming dies, improving the surface quality of structural components, inhibiting quick grain growth and solute-loss from the surface layers, thus resulting in better post-forming mechanical properties. This paper will summarize the dependence of superplasticity on grain size and shape in various metallic materials, including ferrous and non-ferrous alloys, which has been considered as an effective strategy to enable the LTSP.